Trajetória formativa de professores da eja que atuam com estudantes público da educação especial - Lira, Diego Oliveira (2024)
Considering the challenges that guide teacher training, as well as the growing number of enrollments of Public Special Education (PEE) students in common Youth and Adult Education (EJA) classes, the present research had the general objective of analyzing the training trajectory of EJA teachers who work with PEE students, at the Elementary and High School levels. And the specific objectives were: b) identify how the process of continued training of EJA teachers occurs; c) identify the knowledge and demands of EJA teachers in relation to public Special Education students. Eight teachers participated in the study, five male and three female, with ages ranging between 28 and 58 years old. The participants taught at EJA in different schools located in a medium-sized municipality in the northwest region of Ceará and had at least one PAEE student in the classroom. The data collection procedure included individual interviews with a semi-structured protocol, at the teachers' workplace. The interviews were transcribed and validated by judges, with the data organized and analyzed in the form of categorical content analysis. In general terms, among EJA teachers, there was a predominance of initial training in Pedagogy, but with other different degrees, such as Zootechnics; few teachers had experience in participating in continuing or in-service training on the topic of Special Education; the mix of ideas and knowledge that the participating teachers have regarding EJA and Special Education is noticeable, whether through practice or through courses or in-service training; however, there are still deficits in relation to the training of EJA teachers and the need to pay attention to the demands and practices that include Special Education public people inserted in these contexts.